Excess money growth and inflation dynamics - Barbara Roffia; Andrea Zaghini (European Central Bank (ECB), 2007)
The paper analyses the short-run impact of periods of strong monetary growth on inflation dynamics for 15 industrialised economies. We find that, over a 3-year horizon, the positive link between monetary aggregates and prices holds in approximately fifty percent of the cases. An econometric investigation suggests that a contemporaneous increase in the gap measures of the real stock price and real housing price and strong dynamics of loans to the private sector significantly increase the probability of turning an episode of excessive money growth into an inflationary outburst.
Keywords: 330; inflation; money growth; quantity theory of money; Geldmenge; Inflation; Quantitätstheorie; Industrieländer